Experimental study on effects of gas-shielding in lap-fillet arc welding. Issue 10 (2nd December 2021) - Tanaka, Manabu; Yamada, Tetsuo; Shigeta, Masaya; Komen, Hisaya; Fukahori, Mitsugi; Saito, Naoko
ABSTRACT: In order to clarify the relationship between the shielding gas flow and the shieldability during a lap-fillet arc welding, oxygen concentration measurements on a water-cooled copper, which imitated a lap-joint in tungsten inert gas welding were conducted. Moreover, the shielding gas flow and the high-speed plasma flow during the welding were visualized by the Schlieren method and the observation method using a tube tungsten electrode and xenon gas, respectively. As a result, a low-oxygen concentration region, where the oxygen concentration was less than or equal to 100 ppm, was formed on the water-cooled copper. It was suggested that this was because the high-speed plasma flow was separated into the upper side and the lower side of a step, which imitated the lap-joint part, and the intrusion of the atmosphere was prevented by the increase of the velocity of a shielding gas flowing around the plasma flow. When the arc length was set to be long, although the position of the low-oxygen concentration region was changed, there was small difference of the shieldability caused by the difference of the torch angle. However, when the arc length was set to be short and the torch was tilted, the plasma flow was blocked by the step and it did not flow to the upper side of the step. It caused that the shieldability became worse because the low-oxygen concentration region became narrow due to the low-speed shielding gas flowed on the upper side of the step. These results obtained in this study suggested that the shieldability during the welding could be improved by controlling the arc length.